Aspects of romance in Mahmoud Darwish's poetry - Salim Al-Hamadany (آداب الرافدين, 1971)
Romance is not a literary doctrine. As much as it is an expression of a psychological condition. Born by human revolution against all restrictions. I am not among those who see that any literary doctrine ends when another literary doctrine is established, so this remains and that goes. Because none of these doctrines is born and developed by psychological, social and political conditions. It never ends as long as there are souls feeling and moving. And it goes through the same conditions that others go through before. Rather, it is an expression of a certain literary doctrine in Bibi, an expression of the conditions in which he lives. Affects. And is affected. And the literary case is then according to a civilized and humanitarian dictionary that is repeated over the days and years. And if romance was born in France two centuries ago. It is because the political conditions. And the terrible defeat that led to the crushing of the French psyche was the factor that moved the souls of poets and writers to express within this literary doctrine that rebelled against all the restrictions that the classical doctrine was invoking, so the hope that the French people dreamed of was no longer a mirage after the defeat of Napoleon the Great. His dreams were a mirage that does not end with his reality. Hence the expression of poetry from the human self, with all the harsh psychological conditions involved in this self. It is the hope of salvation from thinking about a human setback. And losing his great hope. And the owners of this doctrine did not see dressing up with words. Neither in the choice of expressions, nor in this system that is exquisite in the systems and the tendency behind artificiality is nothing but a reactionary stage in literature, which must be replaced by a literary doctrine that is not bound by restrictions or boundaries. All that distinguishes it is that the poet is free to catch the word. And choose meanings. And free to express the human soul, which, during these circumstances, became a necessity for diving into the depths of literature and art. Hence, romance was an advanced literary stage, which came on the ruins of classicism, but this does not mean that romance remained alone in the field, as symbolism soon came to revolt on this revelation that characterized Romanticism and saw symbolism in this ambiguity, which is one of its best signs of measure. It is measured by art and poetry. Because, in her opinion, disclosure is nothing but a failure to express profound expression that the helpless cannot know.